High levels of both serum gamma-glutamyl transferase and alkaline phosphatase are independent predictors of mortality in patients with stage 4–5 chronic kidney disease - Fernando Caravaca-Fontán; Lilia Azevedo; Miguel Ángel Bayo; Boris Gonzales-Candia; Enrique Luna; Francisco Caravaca (Nefrología (English Edition), 2017)
Introduction: High serum gamma-glutamyl transferase (GGT) levels are associated with increased mortality in the general population. However, this association has scarcely been investigated in patients with chronic kidney disease (CKD). This study aims to investigate the clinical characteristics of CKD patients with abnormally elevated serum GGT, and its value for predicting mortality. Material and methods: Retrospective observational study in a population cohort of adults with stage 4–5 CKD not yet on dialysis. Demographic, clinical, and biochemical parameters of prognostic interest were recorded and used to characterise CKD patients with high levels of GGT (>36 IU/L). Cox proportional hazard regression models were used to analyse the influence of baseline serum GGT and alkaline phosphatase (ALP) levels on mortality for whatever reason. Results: The study group consisted of 909 patients (mean age 65 ± 15 years). Abnormally elevated GGT or ALP levels at baseline were observed in 209 (23%) and 172 (19%) patients, respectively, and concomitant elevations of GGT and ALP in 68 (7%). High GGT levels were associated with higher comorbidity burden, and a biochemical profile characterised by higher serum concentration of uric acid, triglycerides, alanine aminotransferase, ferritin, and C-reactive. During the study period, 365 patients (40%) died (median survival time = 74 months). In adjusted Cox regression models, high levels of GGT (hazard ratio [HR] = 1.39; CI 95%: 1.09–1.78, P = 0.009) and ALP (HR = 1.31; CI 95%: 1.02–1.68, P = 0.038) were independently associated with mortality. Conclusion: High serum levels of GGT are independent predictors of mortality in CKD patients.